2015
DOI: 10.1007/s13197-015-1720-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of germination time of brown rice in relation to flour and gluten free bread quality

Abstract: The effect of germination time on physicochemical characteristics of brown rice flour and its effect on gluten free bread qualities have been investigated. Germination was carried out at 28°C and 100 % RH for 12, 24 and 48 h; brown rice and soaked brown rice was also analyzed. Significant changes on hydration and pasting properties of brown rice flour were found during germination. The starch degradation by enzyme activity could be evidenced with the decrease in viscosity and water binding capacity (WBC). No s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
49
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 36 publications
18
49
2
Order By: Relevance
“…Nevertheless, the difference in the pattern plot suggested additional changes in the doughs containing germinated and toasted chickpea flours. Presumably, activation of enzymes during germination might explain the decrease in C4 and C5 observed in germinated doughs, as has been reported for rice flours (Cornejo and Rosell 2015;Charoenthaikij et al 2009) and oat flour due to increase in the a-amylase, proteolytic and lipolytic activities (Makinen et al 2013). Results obtained for dough containing toasted chickpea flour suggested that thermal treatment modified flour compounds despite the limited amount of water, as confirmed results obtained with the hydration properties.…”
Section: Flour Hydration Propertiessupporting
confidence: 78%
See 1 more Smart Citation
“…Nevertheless, the difference in the pattern plot suggested additional changes in the doughs containing germinated and toasted chickpea flours. Presumably, activation of enzymes during germination might explain the decrease in C4 and C5 observed in germinated doughs, as has been reported for rice flours (Cornejo and Rosell 2015;Charoenthaikij et al 2009) and oat flour due to increase in the a-amylase, proteolytic and lipolytic activities (Makinen et al 2013). Results obtained for dough containing toasted chickpea flour suggested that thermal treatment modified flour compounds despite the limited amount of water, as confirmed results obtained with the hydration properties.…”
Section: Flour Hydration Propertiessupporting
confidence: 78%
“…The specific volume (Table 2) of breads was significantly higher for toasted chickpea bread (1.79 mL/g), followed by raw chickpea and germinated chickpea breads, whereas cooked chickpea flour yielded the lowest specific volume. It was expected that the bread made with germinated flour had higher specific volume, due to the increase in protein solubility, resulting in better emulsifying capacity and foaming properties during germination (Aguilar et al 2015;Mostafa et al 1987), but it has been also described that excessive germinated flours resulted in lower specific bread volume (Cornejo and Rosell 2015). Bread made with cooked chickpea flour had the lower specific volume (0.58 mL/g) that might be ascribed to the reduction of protein solubility caused by denaturation during heating and also to the released of water soluble compounds to the boiling water.…”
Section: Quality Properties Of Breadsmentioning
confidence: 99%
“…The germination of cereal and pseudo‐cereal grains can lead to a drastic increase of α‐amylase. Rice flour with 48 h of germination produces a significant softness in bread crumb, but also results in an excessive liquefaction and dextrinisation causing inferior bread quality (Cornejo & Rosell, ). In a research of Mäkinen et al ., germination of oat presented a drastic increase in α‐amylase activity from 0.3 to 48 U g −1 , and minor increases in proteolytic and lipolytic activities.…”
Section: Other Approaches To Improve Gf Baked and Pasta Qualitymentioning
confidence: 99%
“…The difference in these pasting related Mixolab parameters registered for the samples with different types of soy flour might be explained by the increased amylase activity in the germinated beans. The reduction of torque during heating and cooling is the result of the extensive degradation of starch by amylases activated during germination (Cornejo and Rosell, 2015). The starch gelatinization range (C3-C2) was higher in sample with germinated soy flour (1.23 Nm), compared to the sample with native soy flour (1.09 Nm).…”
Section: Influence Of Germination and Fermentation On The Thermo-mechmentioning
confidence: 99%